Upaya Peningkatan Keterampilan Belajar PAI melalui Metode Demonstrasi pada Anak TK Juita Kinali - Siska Handayani (Kampus Akademik Publiser, 2024)
This study aims to determine the demonstration method can improve student learning skills with prayer material in Tk Juita kinali children in 2024. This class action research uses the demonstration method by practicing or showing children a process, a situation that is being studied so that the process of children's acceptance of the lesson will be more deeply memorable. This research is a PTK with 3 cycles through 4 stages, namely planning, implementation, observation and reflection. The subjects of this study were 30 children. The hypothesis proposed is that if the demonstration method can be used properly, it can improve children's learning skills in PAI subjects in juita kindergarten children in 2024. The success indicator is 75% with a KKM of 75. Data collection techniques with observation. Data analysis techniques with formulas to determine the average value and percentage. The results showed that learning skills in cycle I amounted to 44% or 14 children with KKM 75, cycle II amounted to 56% or 18 children with KKM 75 and in cycle III amounted to 81% or 26 children for prayer rukun material and amounted to 87.5% or 28 children for prayer sunah material with KKM 75. The increase in children's learning skills in cycle I to cycle II amounted to 12% with KKM 75, an increase in skills in cycle II to cycle III with prayer rukun material by 25% and in prayer sunah material by 31.5%.